2015
DOI: 10.1038/ejhg.2014.298
|View full text |Cite
|
Sign up to set email alerts
|

Research participants in NGS studies want to know about incidental findings

Abstract: Following the implementation of high-throughput sequencing legal and ethical issues are discussed intensively. The management of incidental findings (IFs) in a research setting have been investigated but there is a lack of literature concerning research participant's perspective. The aim of this study was to investigate whether research participants want disclosure of IFs and what kind of IFs they want to know about. One hundred and twenty-seven research participants in a study of gastrointestinal polyps were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 22 publications
2
29
1
Order By: Relevance
“…Because the structural abnormalities in the majority of cases were identified by routine ultrasound examination performed at 22–24 gestational weeks and the fetal phenotypes were non‐specific, the multiple diagnoses made highlight the efficiency of prenatal WES. There has been much discussion on how to interpret incidental findings on WES. The 6.1% (12/196) rate of incidental findings in our study again raises this question.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Because the structural abnormalities in the majority of cases were identified by routine ultrasound examination performed at 22–24 gestational weeks and the fetal phenotypes were non‐specific, the multiple diagnoses made highlight the efficiency of prenatal WES. There has been much discussion on how to interpret incidental findings on WES. The 6.1% (12/196) rate of incidental findings in our study again raises this question.…”
Section: Discussionmentioning
confidence: 61%
“…It is expected that a higher rate of incidental findings would occur in prenatal cases compared with postnatal patients (5%) because phenotypic assessments are often inadequate during prenatal diagnosis. Current ACMG guidelines recommend the reporting of incidental results that are associated with diseases that can be managed well with medical intervention, specifically pathogenic variants identified in 59 genes in postnatal patients. However, clinically handling incidental findings on prenatal diagnosis will present greater ethical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Returning these unsolicited findings raises challenges for patients and their family members. Several studies have shown that patients are generally positive about receiving unsolicited findings . This also holds true for cancer patients, but research suggests that patients become more cautious to receive all types of risk information when they are informed about the potential consequences for themselves and their family members .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these individuals also wanted to learn about life-threatening conditions that were not preventable, and overall, participants were more interested in results that confer a higher risk of developing disease. Another study in Denmark showed research participants undergoing genomic sequencing were interested in learning about all incidental findings instead of limiting the disclosure to results that would have a direct impact on medical management (Jelsig et al 2015).…”
Section: Introductionmentioning
confidence: 99%